Guilherme Santos Collection in the Rio de Janeiro Museum of Image and Sound: A Three-Dimensional City (1908-1957) (International Journal on Stereo & Immersive Media, 2018)
This paper aims to present Guilherme Santos’ historical stereoscopic collection, which belongs to the Rio de Janeiro Museum of Image and Sound. As an amateur photographer, Santos widely registered the city of Rio de Janeiro between 1909 and 1957 and his stereoscopic collection is considered one of the most important in Brazil. The historical period in which he developed his work is characterised by the restructuring of Rio de Janeiro as a bourgeois metropolis. The modernised daily life and the new signs of development in the country’s former capital were intensely recorded by Santos during his photography trajectory. As an enthusiast of social life, he was constantly cataloguing the most diverse events, different touristic places and the exuberant nature of the “wonderful city”. Playing the role of a cultural representation of his time, Santos’ photographs give important clues of the shaping of a typically bourgeois lifestyle in Rio de Janeiro.